Composition and Yield of Colostrum and Milk from Murrah and “Murrah x Carabao” Crosses in the Philippines - Bondoc, O. L.; Almendral-Saludes, T.; Tandang, A. G.; Bustos, A. R.; Ramos, A. R.; Ebron, A. O. (Tropical Animal Science Journal, 2021)
This study compared the composition, yield, and freezing point of buffalo colostrum and milk collected on the 30th, 60th, and 90th day of lactation from purebred Murrah and its crosses with the Philippine Carabao. A total of 133 milk samples were collected from 36 buffaloes (20 purebred Murrah and 16 “Murrah x Carabao” crosses) and evaluated for fat, protein, and lactose content, solids non-fat (SNF), total solids, and freezing point. Colostrum contained significantly (p0.05) between colostrum and milk. Colostrum from Murrah buffaloes had more protein but less fat and colostrum yield than “Murrah x Carabao” crosses. Among crossbred buffaloes, the F2 “75% Murrah – 25% Carabao” crosses produced more colostrum than F1 “50% Murrah – 50% Carabao” (p